Hepatitis B and C prevalence in Portugal: disparity between the general population and high-risk groups - Carvalhana, S.C. (2016)
Background and aims: The prevalence of anti-HCV and HBsAg in Portugal has been shown to be elevated in high-risk groups, such as intravenous drug-users and incarcerated individuals. However, in the general population, prevalence remains largely unknown. The aims of this study were to estimate the prevalence of anti-HCV and HBsAg in the general Portuguese population and identify associated risk factors. Materials and methods: We carried out a nationwide, population-based cross-sectional study of adults resident in mainland Portugal. Serology for HBsAg, anti-HBc, anti-HBs, and anti-HCV was performed. Anti-HCV-positive individuals were tested for HCV RNA by PCR. Results: Of 1685 participants, 50.6% were men, mean age 50.2±18.3 years. In terms of hepatitis C, the prevalence of anti-HCV was 0.54% [95% confidence interval (CI): 0.2–0.9] and 0.12% (95% CI: 0.0–0.3) were viremic, with peak prevalence among individuals 35–64 years of age (0.8%), men (0.8%), and individuals from Lisbon and Tagus Valley region (1.9%). In terms of hepatitis B, the estimated prevalence of HBsAg was 1.45% (95% CI: 0.9–2.0). A higher prevalence was found in individuals who were 35–64 years old (2.2%), in men (2.5%), and in the Northern region (2.6%). The presence of positive serological markers of hepatitis C virus and hepatitis B virus infection did not correlate with elevated aminotransferases, race, place of birth, and alcohol consumption. Conclusion: These results suggest a low endemicity for both hepatitis B and hepatitis C in the general population, in contrast to a very high prevalence in risk groups, thus suggesting that targeted screening to high-risk groups may be more cost-effective than general population screening.